Physicochemical, Surface and Catalytic Properties of CoO/AlO as Influenced by CeO or VO Doping - H.G. El-Shobaky (Adsorption Science & Technology)
A pure Co 3 O 4 /Al 2 O 3 sample was prepared by the wet impregnation method using finely powdered aluminium hydroxide and cobalt nitrate dissolved in the least amount of distilled water. Maintaining the amount of Co 3 O 4 constant at 16.7 mol%, different samples were doped by impregnating with known amounts of cerium or vanadium nitrates prior to impregnation with cobalt nitrate. The pure and doped samples were precalcined at 600°C and 800°C, respectively. The dopant concentrations employed were 0.5, 1.0, 2.0 and 3.0 mol% CeO 2 or V 2 O 5 . The resulting materials were studied by XRD and EDX methods, N 2 adsorption at −196°C and CO oxidation by O 2 at 130–220°C. The results obtained revealed that the surface concentrations of cobalt species in pure and variously doped Co 3 O 4 /Al 2 O 3 solids precalcined at 600°C were more than twice those present in the bulk of these solids. Heating the doped solid at 600°C and 800°C increased the degree of dispersion of Co 3 O 4 by decreasing the crystallite size. This effect was more pronounced in the case of V 2 O 5 doping, with the surface concentration of cobalt species being increased to a greater extent than with CeO 2 doping. Similarly, heating the doped solid at 600°C resulted in a progressive but measurable increase in the lattice parameter of Co 3 O 4 due to the formation of solid solutions. On heating the V 2 O 5 -doped solid at 800°C, a portion of the added V 2 O 5 inter-acted with Co 3 O 4 to yield cobalt vanadate while the other portion contributed to the formation of a solid solution. Doping followed by heating at 600°C increased the catalytic activity of the doped solids in CO oxidation by O 2 . In contrast, solids precalcined at 800°C exhibited the opposite effect. The doping process changed the concentration of active sites involved in the catalytic reaction rather than changing the mechanism of the catalytic reaction.